PENINGKATAN KEBUGARAN TUBUH SISWA MELALUI SENAM IRAMA SEKOLAH DASAR - Sembiring, Heka Maya Sari Br; Ndruru , Cindi Triani; Sitinjak , Putriani; Jhosephine, Jesicca; Ginting , Eden Elyezer (PUAN INDONESIA, 2025)
Rhythmic gymnastics is a sport that combines body movements with music, aimed at improving physical fitness, coordination, and motor coordination. At SDN 013 BONGAN, rhythmic gymnastics is implemented as part of the Physical Education, Sports, and Health (PJOK) curriculum. This article reviews the implementation of rhythmic gymnastics at SDN 013 BONGAN, including teaching methods, benefits for students, and challenges in its implementation. This study shows that rhythmic gymnastics can improve students' fitness while supporting the development of their creativity and self-confidence. Although there are challenges such as limited facilities and teacher competence, ongoing efforts to improve the quality of learning, such as teacher training and providing more adequate space, can help optimize the results achieved. With good management, rhythmic gymnastics can continue to be an important part of PJOK learning at SDN 013 BONGAN and other schools.